Phenytoin toxicity with mandibular tremor secondary to intravenous administration - (:unkn) unknown (DUSTRI-VERLAG DR KARL FEISTLE, 2002)
The parenteral form or phenytoin is the most commonly used antiepileptic agent during the perioperative period in neurosurgery clinics. We report observations in a 52-year-old male patient with hypoalbumin-emia and phenytoin intoxicity following I day preoperative administration and a 7-day postoperative intravenous administration of the drug with no modification of the oral dose. This report emphasizes the need for careful surveillance of phenytoin-induced toxicity during parenteral therapy, especially in debilitated patients.
Keywords: phenytoin toxicity; mandibular tremor; hypoalbuminemia